Policy Implementation in Indonesia: A Systematic Review of Recent Trends and Practices in Public Administration and Governance - Nomensen Yeheskel Singgir; Dian Ferriswara; Ika Devy Pramudiana; Sri Kamariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study presents a systematic literature review (SLR) of public administration and policy implementation in Indonesia from 2009 to 2025, following the PRISMA framework. Drawing on 44 peer-reviewed articles indexed in Scopus, the review examines the impact of decentralization, digital transformation, and governance innovation on policy outcomes and administrative reform. The findings indicate that decentralization has enabled local experimentation and improved service responsiveness. However, it has also resulted in uneven policy capacity and governance disparities across regions. Sectoral implementation, especially in health, welfare, and food safety, remains inconsistent, largely due to institutional fragmentation, political interference, and capacity limitations. Although efforts to implement New Public Management (NPM) principles and digital tools have been made, bureaucratic inertia, coordination failures, and limited flexibility hinder reform progress. The rise of e-government and agile governance shows promise in enhancing efficiency and public participation. However, these advancements are still hampered by digital divides and regulatory uncertainties. The COVID-19 pandemic further exposed critical vulnerabilities in policy execution, underscoring the need for resilient, adaptive governance models capable of responding to unforeseen crises. This review contributes to the understanding of Indonesia’s evolving administrative landscape and offers several practical recommendations. These include strengthening intergovernmental coordination, investing in local administrative capacity, fostering participatory governance, and institutionalizing agile, collaborative practices. The study highlights the importance of integrated, inclusive, and data-driven governance to improve public sector performance and ensure democratic accountability. By focusing on these areas, Indonesia can better address the challenges of public administration and policy implementation, driving long-term sustainable development and effective governance in the country.